1996
DOI: 10.1136/qshc.5.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Adapting total quality management for general practice: evaluation of a programme.

Abstract: Objective -Assessment of the benefits and limitations of a quality improvement programme based on total quality management principles in general practice over a period of one year (October 1993 -4 Traditional audit is limited in achieving and showing overall service improvement in primary care.' 2 This is largely because audit tends to be topic based, retrospective, and usually involves few members of the primary healthcare teams.2 3 Total quality management seems to offer a more comprehensive approach to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…These findings are congruent with those of earlier research where the provision of protected time is seen as an essential prerequisite to many quality improvement activities (Grol and Wensing, 1995;Chambers et al, 1996;Lawrence and Packwood, 1996;Hearnshaw et al, 1998;Johnston et al, 2000). However, protected time for part-time staff is less easily achieved and further approaches to ensuring protected time for these practice team members needs to be pursued.…”
Section: Protected Timesupporting
confidence: 93%
“…These findings are congruent with those of earlier research where the provision of protected time is seen as an essential prerequisite to many quality improvement activities (Grol and Wensing, 1995;Chambers et al, 1996;Lawrence and Packwood, 1996;Hearnshaw et al, 1998;Johnston et al, 2000). However, protected time for part-time staff is less easily achieved and further approaches to ensuring protected time for these practice team members needs to be pursued.…”
Section: Protected Timesupporting
confidence: 93%
“…18 19 As they build their knowledge about how things currently work, such groups are likely to discover that their difficulties are more often derived from the processes they use than from each other. A recent study in Oxford showed that one consequence of establishing multiprofessional improvement teams in general practices was increased collaboration and focus on planning and strategy within the practices 20. A powerful incentive for greater teamwork among professionals is created by directing attention to the areas where changes are likely to result in measurable improvements for the patients they serve together, rather than concentrating on what on the surface seem to be irreconcilable professional differences.…”
Section: Making Interprofessional Collaboration and Teamwork A Realitymentioning
confidence: 99%
“…1 2 Continuous quality improvement has advantages over former profession oriented models for quality assurance because it combines managerial and collaboration aspects with a systematic approach. [3][4][5] In another paper in this issue we present a model for continuous quality improvement in small scale general practice. This model was based on core elements of continuous quality improvement, which were identified as management, collection of factual data, systematic approach, and collaboration.…”
mentioning
confidence: 99%